PENGARUH EXPERIENTAL VALUE DAN PLACE FOOD IMAGE TERHADAP BEHAVIORAL INTENTION WISATA KULINER BANDUNG - Inad Wasa Nugroho; Siti Rahayu; Erna Andajani (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
Every tourist has a different motivation. One type of tourism that is currently growing very rapidly is the culinary industry. This study is to determine the experiential value of tourists in shaping the place food image of the city of Bandung and influencing behavioral intention. This causal type of quantitative research analyzes data using the Structural Equation Model equation. The results of the study found evidence of all research hypotheses proved to have a positive and significant influence relationship.